The temporal nominative in the Baltic languages (Atti del Sodalizio Glottologico Milanese, 2025)
In the Indo-European languages, the nominative is generally considered a purely grammatical case, excluded from circumstantial functions. There are, however, in the Baltic languages, circumstantial uses of the nominative in certain temporal expressions, e.g. Lithuanian jau mėnuo tėvas serga ‘the father has been ill for a month; it is one month that the father has been ill’ (nominative singular mėnuo). The aim of this paper is to present the specific uses of the temporal nominative in the Baltic languages and to explain their origin. A comparison with Greek and Latin shows the antiquity of the construction with the nominative. Three explanations of the temporal nominative can be suggested: (1°) ellipsis of a conjunction (‘already one monthNOM.SG [that] the father is ill’), (2°) syntactic contamination (‘already one monthNOM.SG that the father is ill’ x ‘during one monthACC.SG the father is ill’) or (3°) inclusion of a parenthetical structure (‘it is already one monthNOM.SG, the father is sick’). The last explanation would rely on parallels from other Indo-European languages, notably the Latin type nudius tertius ‘two days ago’ < ‘now [it is] the third day’.